ANALISIS KINERJA SIMPANG TAK BERSINYAL DI SIMPANG 3 GANTING DEKAT MTsN 1 KOTA PADANG PANJANG - Saputra Agam, Rahul; Gusmulyani, Gusmulyani; Dewi, Selpa (Ensiklopedia Research and Community Service Review, 2024)
A road intersection is a place for traffic flow from two or more roads to meet. The performance of the intersection must take into account the delay due to the existence of both signalless and signalized intersections. At unsignalized intersections there is congestion caused by side barriers, the high number of vehicles that are not matched by the availability Adequate road infrastructure. Analyzing the capacity and level of performance of an unsignalized intersection requires data from the field, in the form of intersection geometric data (width of each foot of the intersection), type and number of vehicles crossing the intersection after being multiplied by the passenger car equivalent number ( emp), so that the value in passenger car units (SMP) is obtained. Then the capacity and performance level of the intersection is calculated which includes the degree of saturation and delay of the intersection using the Indonesian Road Capacity Manual method (MKJI 1997). The results of the analysis showed that the capacity value (C) was 2321.033 pcu/hour, the degree of saturation (DS) was 0.41 sec/pcu, and the delay value (D) was 3.022 sec/pcu. Then obtained the level of service at the intersection of Jl. The Padang-Bukit Tinggi Sumatra route is still able to accommodate traffic volumes, because the degree of saturation (DS) is still small and the level of delay assessment is still in criterion C, so there is no need to re-calculate at the Jl. Cross Sumatra Padang - Bukittinggi. Keyword : Unsignalized intersection,road ferformance,side barrier, intersection, kapacity